Perancangan Aplikasi Keamanan Pesan Audio Dengan Metode CAST-256 - Elprida Hutahaean (STMIK Budi Darma, 2020)
Cryptography is the science or art of learning how to make a message sent by the sender safely delivered to the recipient. Cryptography is part of a branch of mathematics called cryptology (cryptology). Cryptography aims to maintain the confidentiality of information contained in data so that information can not be known by unauthorized parties. The designer of a cryptographic algorithm is called a cryptographer. This makes information a material that must be kept confidential. One way to exchange information is to use electronic messages. The Cast method is a block cipher algorithm that has been used in various products such as the pgp example. The Cast method is the key to symmetry. Audio files are sound samples of sound, every fraction n one second, sound samples are stored as digital information in dit and bytes. Audio is material containing messages in auditive form (vocal cords or voice plates), which can design thoughts, feelings, concerns, and student's will so that the learning process occurs. Audio is a physical phenomenon produced by the vibration of an object in the form of an analog signal with an amplitude that changes continuously with respect to a unit of time called frequency